2017
DOI: 10.1186/s12903-017-0436-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of visits and examinations in the Public Dental Service in Finland – a retrospective analysis, 2001–2013

Abstract: BackgroundThis study aimed to investigate longitudinally examination and visiting patterns in the Finnish Public Dental Service (PDS) and to relate these to patients’ treatment needs and international recommendations on examination intervals.MethodsData on patients and their dental visits in the period 2001–2013 were collected from five municipal PDS-units serving a total population of 320,000 inhabitants and using the same database system. Ethical approval was given by the National Institute for Health and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
(6 reference statements)
1
13
0
Order By: Relevance
“…Our finding that having dental insurance was associated with a greater likelihood of seeking future dental care was consistent with research from other countries, including studies from Korea [ 41 ] and Finland [ 42 ] showing an increase in dental visit attendance after a nationwide expansion in public dental insurance coverage. In the U.S., only about 7% of adults have public dental insurance (provided through Medicaid) and about 60% have private dental insurance, usually obtained through their employer or on the individual insurance market [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that having dental insurance was associated with a greater likelihood of seeking future dental care was consistent with research from other countries, including studies from Korea [ 41 ] and Finland [ 42 ] showing an increase in dental visit attendance after a nationwide expansion in public dental insurance coverage. In the U.S., only about 7% of adults have public dental insurance (provided through Medicaid) and about 60% have private dental insurance, usually obtained through their employer or on the individual insurance market [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…The trend towards increasing total numbers of treatment measures among the “healthy young” is worrying, especially when politically there has been a desire to improve adults’ access to the PDS. An earlier study showed that the young were five times more likely to be examined in the PDS than adult patients although they were three times less likely to be in need of care [16]. A law enacted in 2011 requires two dental examinations before a child reaches 7 years old and three more examinations before the age of 18 years [17].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all the young people in Finland (99%) use the PDS [6]. Throughout the study period, the annual coverage (proportion of the population that attended the PDS) of children and adolescents was high, around 75% [16]. During the study period, the number of dental hygienists doubled (+ 97.9%) and the number of dentists did not change (− 0.0%).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that from 2001 to 2013, the number of adults (18+ years) treated in the participating PDS-units increased by 81.5%. In 2001, the shares of young (<18 years) and adult patients were 51.5% and 48.5% respectively and in 2013 these were 36.8% and 63.2% [23]. This Overall, during the 13-year study period, most adults living in the local municipalities (77.5%) had visited the PDS on some occasion.…”
Section: Discussionmentioning
confidence: 82%